Talent Management and Knowledge Management Effects on Employee Performance: The Mediating Role of Job Satisfaction: (A Study on Employees of Yayasan Bina Tani Sejahtera) - Faqih Ahmadi, Abi Fiqri; Istanti, Fredianaika (Universitas Pamulang, 2026)
This study aims to analyze the role of job satisfaction as a mediating variable in the relationship between talent management, knowledge management, and employee performance. Effective human resource management is considered essential in ensuring the alignment between employee competencies and job placement in order to enhance performance. This study adopts a quantitative approach involving 65 employees of the Bina Tani Sejahtera Foundation distributed nationally, using a simple random sampling technique. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that talent management and knowledge management have a positive and significant effect on employee performance, both directly and indirectly through job satisfaction. These findings confirm that job satisfaction serves as a significant partial mediator, underscoring the importance of job satisfaction in strengthening the effectiveness of organizational talent and knowledge management practices. Theoretically, this study contributes to the human resource management literature by enriching the understanding of job satisfaction as a mediating mechanism. Practically, the findings provide implications for the management of the Bina Tani Sejahtera Foundation to reinforce talent management and knowledge management practices as sustainable strategies for enhancing employee satisfaction and performance.